Development of a two-part biomaterial adhesive strategy for annulus fibrosus repair and ex vivo evaluation of implant herniation risk. (November 2020) - DiStefano, Tyler J.; Shmukler, Jennifer O.; Danias, George; Di Pauli von Treuheim, Theodor; Hom, Warren W.; Goldberg, David A.; Laudier, Damien M.; Nasser, Philip R.; Hecht, Andrew C.; Nicoll, Steven B.; Iatridis, James C.
Abstract: Intervertebral disc (IVD) herniation causes pain and disability, but current discectomy procedures alleviate pain without repairing annulus fibrosus (AF) defects. Tissue engineering strategies seal AF defects by utilizing hydrogel systems to prevent recurrent herniation, however current biomaterials are limited by poor adhesion to wetted tissue surfaces or low failure strength resulting in considerable risk of implant herniation upon spinal loading. Here, we developed a two-part repair strategy comprising a dual-modified (oxidized and methacrylated) glycosaminoglycan that can chemically adsorb an injectable interpenetrating network hydrogel composed of fibronectin-conjugated fibrin and poly (ethylene glycol) diacrylate (PEGDA) to covalently bond the hydrogel to AF tissue. We show that dual-modified hyaluronic acid imparts greater adhesion to AF tissue than dual-modified chondroitin sulfate, where the degree of oxidation is more strongly correlated with adhesion strength than methacrylation. We apply this strategy to an ex vivo bovine model of discectomy and demonstrate that PEGDA molecular weight tunes hydrogel mechanical properties and affects herniation risk, where IVDs repaired with low-modulus hydrogels composed of 20kDa PEGDA failed at levels at or exceeding discectomy, the clinical standard of care. This strategy bonds injectable hydrogels to IVD extracellular matrix proteins, is optimized to seal AF defects, and shows promise for IVD repair.